Pelatihan Pembuatan Eco Fire sebagai Solusi Pengurangan Asap Hasil Pembakaran Sampah di Desa Pandansari Kedungjajang Lumajang - Jauhani, Muhammad Afiful; Suputra, Gede Ngurah Darma; Ramli, Muhammad Yusril Kaisar; Qurratu’aini, Nazhifah; Dewa Made Rivaldo Krisna Subagia Putra; Frendy Wahyu Hermawan; Sultan Akbari Wijaya; Muhammad, Mahathir Zakaria Adi; Aura Fortuna; Aisyah Dhivta Silvia Effendhie; Bayu Ahmad Dhani; Qanidatul Mukaromah (Fakultas Kedokteran Gigi, Universitas Jember, 2025)
Waste management is a major challenge in Pandansari Village, Kedungjajang District, Lumajang Regency, particularly due to sugarcane farming waste (dry leaves) and household waste, which are commonly burned in the open. This practice produces thick smoke that negatively affects air quality, public health, and road safety. The issue aligns with growing concerns over environmental health, especially as air pollution increases due to human activities such as open waste burning. This community service program aims to offer a more effective, efficient, and environmentally friendly waste management solution through the design and training of a low-smoke waste incinerator. The program’s partners include the village authorities and residents of Pandansari. Activities were carried out using participatory methods to involve the community at every stage, along with demonstrations to teach the technical skills for building, operating, and maintaining the device. The results show that the incinerator significantly reduces smoke emissions, is easy to operate, and has economic potential through production and sales opportunities. This innovation is important as it demonstrates anenvironmentally friendly technology that can be adapted and replicated in other regions facing similar waste management challenges.Keywords: Community service, waste management, low-smoke waste incinerator, environmentally friendly technology.